Human NK cells confer protection against HIV-1 infection in humanized mice - Can M. Sungur; Qiankun Wang; Ayşe N. Ozantürk; Hongbo Gao; Aaron J. Schmitz; Marina Cella; Wayne M. Yokoyama; Liang Shan (The Journal of Clinical Investigation, 2022)
The role of NK cells against HIV-1 infections remains to be elucidated in vivo. While humanized mouse models potentially could be used to directly evaluate human NK cell responses during HIV-1 infection, improved functional development of human NK cells in these hosts is needed. Here, we report the humanized MISTRG-6-15 mouse model, in which NK cells were quick to expand and exhibit degranulation, cytotoxicity, and proinflammatory cytokine production in nonlymphoid organs upon HIV-1 infection but had reduced functionality in lymphoid organs. Although HIV-1 infection induced functional impairment of NK cells, antiretroviral therapy reinvigorated NK cells in response to HIV-1 rebound after analytic treatment interruption. Moreover, a broadly neutralizing antibody, PGT121, enhanced NK cell function in vivo, consistent with antibody-dependent cellular cytotoxicity. Monoclonal antibody depletion of NK cells resulted in higher viral loads in multiple nonlymphoid organs. Overall, our results in humanized MISTRG-6-15 mice demonstrated that NK cells provided direct anti–HIV-1 responses in vivo but were limited in their responses in lymphoid organs.